General Problems Experienced by Elementary Classroom Teachers - A. Manaf, Zulkifli (Universiti Putra Malaysia Press, 1996)
This study presents the frequency and bother someness of some general problems of a sample of elementary school teachers (n = 439) in a Midwest state, USA. The problems are from self-reports of teachers measured using the abridged version of the teacher problem checklist. The top five problems of elementary school teachers reported in the study are: (I) insufficient preparation time; (2) insufficient time to teach and also to diagnose and evaluate teaching; (3) insufficient free time; (4) motivating students to use their leisure time well, and (5) motivating students to enjoy learning for its own sake. It was also found that the same top five problems bothered all the teachers.